Evaluation on Indonesian’s Local Government Website for Practicing Paradiplomacy - Surwandono Surwandono; Ariyanto Nugroho; Muhammad Dedy Yanuar (Departemen Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik, Unair, 2021)
Paradiplomacy as an instrument of local governments to develop international cooperation in the era of industrial revolution 4.0 requires some thoughts and policies relevant to information technology. Website constitutes an important platform for local governments to exercise their Paradiplomacy as a regional practice of conducting international relations. The website becomes a world window for local governments to communicate and cooperate with local government partners and institutions abroad. This article conducts an evaluation study towards local government websites in Indonesia related to the readiness to face the industrial revolution 4.0 in the issue of international cooperation through digital diplomacy means. The preferred research method is to analyze the content of website structure of the Indonesian local government, be it from front-line, content, and/or backline. This article found that the platform of Indonesian local government websites is fairly fragile in the institutionalization of paradiplomacy using website as the instrument. Comprehensive policies from the central and local governments eventually become indispensable in order to make the practice of digital diplomacy by local governments in Indonesia more productive.Keywords: Paradiplomacy, Digital Diplomacy, e-GovernmentParadiplomasi sebagai instrumen pemerintah daerah untuk mengembangkan kerja sama internasional di era revolusi industri 4.0 memerlukan beberapa pemikiran dan kebijakan yang relevan dengan teknologi informasi. Website merupakan platform penting bagi pemerintah daerah untuk melaksanakan Paradiplomasi mereka sebagai praktik regional dalam melakukan hubungan internasional. Website menjadi jendela dunia bagi pemerintah daerah untuk berkomunikasi dan bekerja sama dengan mitra dan lembaga pemerintah daerah di luar negeri. Artikel ini melakukan kajian evaluasi terhadap website pemerintah daerah di Indonesia terkait kesiapan menghadapi revolusi industri 4.0 dalam isu kerja sama internasional melalui sarana diplomasi digital. Metode penelitian yang dipilih adalah dengan menganalisis isi dari struktur website pemerintah daerah Indonesia, baik dari front-line, content, dan/atau backline. Artikel ini menemukan bahwa platform website pemerintah daerah Indonesia cukup rapuh dalam pelembagaan paradiplomasi dengan menggunakan website sebagai instrumennya. Kebijakan yang komprehensif dari pemerintah pusat dan daerah pada akhirnya menjadi sangat diperlukan agar praktik diplomasi digital oleh pemerintah daerah di Indonesia semakin produktif.Kata-kata kunci: Paradiplomasi, Diplomasi Digital, e-Government